From men to the media and back again : an analysis of mediated help-seeking : a thesis submitted in partial fulfilment of the requirements for the degree of Master of Science in Psychology (with endorsement in health psychology) at Massey University, New Zealand, 2011 - Anstiss, David; Anstiss, David (Massey University, 2011)
Life-expectancy and mortality statistics position the health of western men as in crisis. Not only has popular media facilitated this notion of crisis, the media has played an active role in creating the views that this crisis is ‘fact,’ that men are unwilling to accept responsibility for their own health, and that change is inconceivable. However, although many men have indeed been found to be reluctant to seek help from these services despite wanting to, instances of seeking help do exist and even occur against a social backdrop that seems to actively deter it. In response, this thesis sought and examined a sample of help-seeking texts, written by men, with the aim of uncovering discourses that might be empowering to men in regards to their health and healthy lifestyles. Two discourses emerged that reflect predominant enactments of western versions of masculinities, particularly hegemonic masculinity. Firstly, the biomedical discourse allows men to position themselves, relative to experts, in a way that appears to elicit health information and control consultation directions. Secondly, the (re)establishing masculinity discourse allows men to position themselves as masculine where their masculinity might be threatened. Implications of these discourses are discussed.
Keywords: Men's health; Media and health; Health behaviour; Masculinity